ON THE EXACT SOLUTION ON A LINEAR DIFFERENTIAL EQUATION OF FIRST ORDER - Dimov, Lazo A.; Piperevski, Boro M.; Hadzieva, Elena (Matematichki Bilten, 2014)
We are considering the linear differential equation of first order\[f(x)y' - f'(x)y = f^3(x)R(x,t), \qquad t=\sqrt{a_4x^4+a_3x^3+a_2x^2+a_1x+a_0},\]where \(R(x,t)\) is a rational function. We are giving a condition for the equation to have exact solution and a method for finding the solution.